Inclusive education and research through African Network of Women in Astronomy and STEM for GIRLS in Ethiopia initiatives - Povi, Mirjana; McBride, Vanessa; Muheki, Priscilla; Govender, Carolina O dman; Saad, Somaya; Klutse, Nana Ama Brown; Tsegaye, Aster; Getachew, Tigist; Kelemu, Melody; Kibret, Hanna; Tamirat, Jerusalem; Teka, Deborah Telahun; et al. (Proceedings of the International Astronomical Union, 2019)
The African Network of Women in Astronomy and STEM for GIRLS in Ethiopia initiatives have been established with aim to strengthen the participation of girls and women in astronomy and science in Africa and Ethiopia. We will not be able to achieve the UN Sustainable Development Goals without full participation of women and girls in all aspects of our society and without giving in future the same opportunity to all children to access education independently on their socio economical status. In this paper both initiatives are briefly introduced
Keywords: Astronomy; Women and girls in science